2015
DOI: 10.1017/s0030605315000666
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption patterns of the Vulnerable Socotra cormorant Phalacrocorax nigrogularis indicate minimal overlap with fisheries in the eastern Arabian Gulf

Abstract: Historically cormorants have come into direct conflict with fisheries because of their feeding habits. The Socotra cormorant Phalacrocorax nigrogularis is a regionally endemic seabird restricted to the Arabian Gulf and coastal Oman, and is categorized as Vulnerable on the IUCN Red List. The species is perceived as being detrimental to local fisheries and is therefore persecuted. We studied the diet and estimated the number of Socotra cormorants breeding on Siniya Island, Umm Al Quwain, United Arab Emirates, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although it is known that Socotra Cormorant are important for the cycling of nutrients which is vital for the maintenance of pelagic communities including fish stock (Aspinall 1995), the public perception of the species as a competitor remains unchanged. The species is known to consume sardine Sardinella longiceps (Aspinall 1995) but recent studies from UAE has shown that seven species of fish that are consumed do not overlap with the commercial fisheries (Muzaffar et al 2015). Creating awareness of this misconception about the species being a competitor, and its importance in maintaining a healthy ecosystem and benefits for fisheries, is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that Socotra Cormorant are important for the cycling of nutrients which is vital for the maintenance of pelagic communities including fish stock (Aspinall 1995), the public perception of the species as a competitor remains unchanged. The species is known to consume sardine Sardinella longiceps (Aspinall 1995) but recent studies from UAE has shown that seven species of fish that are consumed do not overlap with the commercial fisheries (Muzaffar et al 2015). Creating awareness of this misconception about the species being a competitor, and its importance in maintaining a healthy ecosystem and benefits for fisheries, is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Socotra cormorants target anchovy, bluestripe herring, and African sailfin flying fish in the eastern Arabian Gulf (Muzaffar et al., ). Assuming they ate mainly anchovy (Muzaffar et al., ), the total fish consumption of Socotra cormorants from Siniya Island (including nonbreeders) during a breeding season amounted to 5,078 tonnes (range: 3,506–7,263 tonnes) or 47 tonnes per day on average (range: 33–68 tonnes) (Appendix S1). Considering the geographic consistency of the foraging area throughout the day, these results imply that the fish school (or schools) exploited by cormorants on a daily basis are of considerable size.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary analyses at the colony have shown that Socotra cormorants forage on shoaling fish, mainly anchovy ( Encrasicholina spp. ), bluestripe herring ( Herklotsichthys quadrimaculatus ), and African sailfin flying fish ( Parexocoetus mento ), suggesting little overlap with local fisheries (Muzaffar et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Being a social forager, carpet-like flocks of tens of thousands of birds move whilst fishing across the shallow parts of this region of the Gulf, perfectly timed so as to meet the congregations of pelagic fish here. The nearby Siniya Island is one of the strongholds of the population, with an estimated 40,000 breeding pairs (over 100,000 birds) that congregate on the ground (Muzaffar 2015).…”
mentioning
confidence: 99%